A pair of rollers for crushing machine and a manufacturing method thereof

By surfacing the medium-carbon alloy steel solid core welding wire containing nano-oxide particles on the roller body of the roller crusher, a working layer with high strength, high wear resistance and good toughness is formed, which solves the problem that existing roller bodies are prone to pits or grooves when crushing medium and high hardness materials, significantly extends the service life and reduces production costs.

CN116139990BActive Publication Date: 2025-04-18JINGXI MEIBANG (BEIJING) SPECIAL STEEL TECH DEV CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310020381.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2025-04-18
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

The roller body of the existing roller crusher is prone to pits or grooves when crushing medium and high hardness materials, resulting in increased wear and short service life, and high-carbon and high-chromium alloy cast iron has high brittleness, making it difficult to meet the requirements of high-precision rollers.

Method used

The casting roller body of ordinary carbon steel or low alloy steel is used to surmount the surface of medium carbon alloy steel solid core welding wire containing nano-oxide particles to form a working layer with high strength, high wear resistance and good toughness.

Benefits of technology

It significantly extends the service life of the rollers, improves wear resistance and toughness, reduces resource waste and production costs, and avoids wear problems caused by insufficient hardening of high manganese steel rollers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116139990B_ABST
    Figure CN116139990B_ABST
Patent Text Reader

Abstract

The present invention relates to a pair of rollers for a crusher and a manufacturing method thereof. The pressure rollers of the pair of rollers include a roller body and a working layer attached to the surface of the roller body; the roller body is cast from carbon steel or low alloy steel, the working layer contains 2.0-2.5% of nanoparticles, 0.36-0.55% of carbon, 4.6-13.5% of chromium, 0.2-1.2% of silicon, 0-1.2% of molybdenum, 0-1.2% of vanadium, 0.3-0.8% of manganese, and the contents of sulfur and phosphorus are less than 0.02% respectively, and the remainder is iron; the composition of the nanoparticles is one or two of aluminum oxide, titanium dioxide, Y2O3, ZrO2, MgO, TiN, BN, MnS·Al2O3, MnS·TiO2, and TiN·MgO·Al2O3. The present invention not only has high strength and hardness, good wear resistance, but also has good toughness, thus overcoming the shortcomings of the existing high manganese steel single-element roller body due to insufficient work hardening ability, such as easy wear and groove formation, short service life, and insufficient production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to a method for manufacturing a pair of rollers for a roller crusher, and in particular to a method for manufacturing a pair of precision rollers which are long-life and renewable for crushing ore with a particle size of ≤3 mm (fine powder), and which are obtained by submerged arc welding using a solid welding wire drawn from nano-oxide-reinforced steel to obtain high strength and high wear resistance. Background technology:

[0002] Roller crusher is a common crushing equipment widely used in metallurgy, mining, building materials, ceramics, abrasives and other industries. The roller of traditional roller crusher is generally cast with high manganese steel. The purpose is to use the austenite structure in high manganese steel to produce a work-hardening layer when the roller surface is strongly squeezed or impacted by external force, so as to achieve external hardness and internal toughness, so as to obtain good use effect. However, during the working process, due to the insufficient extrusion force when crushing the material, the work-hardening layer on the surface of the roller is not obvious, which not only reduces the wear resistance of the roller, but also easily produces pits or grooves on the surface of the roller when crushing hard materials such as corundum. Long-term use can easily lead to fatigue peeling on the surface of the roller, aggravating the wear of the roller and greatly shortening its service life. Although online local surfacing maintenance can extend the service life of the roller, repeated maintenance will cause the roller to deform or even scrap (Yang Binghua, Application of high chromium roller to roller crusher in phosphate ore processing, Sulfur and phosphorus design and powder engineering, 2014, 3: 35-37). The composite roller body (Chen Xuecai, CN106140380A "A Super Wear-Resistant Roller Crusher Composite Roller Body"; Chen Bo et al., "Use and Maintenance of Ceramic Production Roller Crusher", Ceramics, 2008, 11: 40-44) is designed to achieve the purpose of hard outside and soft inside. However, although high carbon high chromium cast iron has high hardness and good wear resistance, it is brittle. When crushing some high hardness materials, it is very easy to cause the high hardness outer roller ring material to peel off and crack, so it is difficult to achieve a very ideal effect. Although the high-hardness wear-resistant layer is welded on the outer layer of the cast steel roller, it has achieved good results when crushing materials with lower hardness. However, these wear-resistant layers are still high-carbon and high-chromium alloys and cannot be cold-drawn. Therefore, flux-cored wires or coated electrodes are often used (Tian Dabiao et al., "Selection of flux-cored wires for submerged arc welding of rollers in brick factories and determination of welding process", China Building Materials Equipment, 1997. 6: 22-23; Ying Pengzhan, "Development of wear-resistant cladding electrodes for roller crushers", Welding Technology, 1998, 1: 22-23; Chen Bo et al., "Use and maintenance of roller crushers in ceramic production", Ceramics, 2008, 11: 40-44) to repair the roller body. There are the following problems: First, it is difficult to achieve uniform microstructure and performance of each part after cladding with flux-cored wires or coated electrodes made of raw materials with different components. When crushing high-hardness materials, the brittleness often causes premature failure of the cladding layer. Second, high-carbon high-chromium alloy cast iron has a high hardness, which can easily lead to cracks in the cladding layer during cladding. Although there are no requirements for transverse cracks in the weld bead on many primary crushing equipment, in many other more delicate working conditions, more specific and stringent specifications are made for the size and direction of the cracks, and even whether they exist. In addition, the poor machining performance of high-carbon high-chromium cast iron also makes it difficult to meet the technical requirements of high-precision rollers.Therefore, when crushing fine powder materials with medium and high hardness, people often cast thicker high manganese steel rollers, and disassemble rollers that have obvious pits or grooves after a certain period of use, and use the bottom of the pits or grooves as a reference to remove the raised part of the roller surface by turning to meet the use requirements. Since this secondary processing method is to remove the working layer on the surface of the roller, the above process can only be repeated twice at most, and a roller cannot be used anymore and is scrapped, which not only increases the labor intensity of workers, but also has a great impact on the production efficiency and cost of the enterprise. Summary of the invention:

[0003] In view of the shortcomings of the current technology, the purpose of the present invention is to provide a method for manufacturing a high-strength precision roller for crushing medium-high hardness ≤3mm (fine powder) ore, which has good wear resistance, is not easy to crack, has a long service life, and is low-cost. The roller body is cast from ordinary carbon steel or low alloy steel, and the working layer is made of submerged arc surfacing with solid welding wire of medium carbon alloy steel containing nano oxide particles. The present invention not only has high strength and hardness, good wear resistance, but also has good toughness, thereby overcoming the shortcomings of the existing high manganese steel single-substance roller body due to insufficient work hardening ability, such as easy wear and groove formation, short service life, and insufficient production efficiency.

[0004] The technical solution adopted by the present invention is:

[0005] A pair of rollers for a crusher, wherein the pressure rollers of the pair of rollers comprise a roller body and a working layer attached to the surface of the roller body; the thickness of the working layer is 9 to 10 mm;

[0006] The roller body is cast from carbon steel or low alloy steel, the working layer contains 2.0-2.5% nanoparticles, 0.36-0.55% carbon, 4.6-13.5% chromium, 0.2-1.2% silicon, 0-1.2% molybdenum, 0-1.2% vanadium, 0.3-0.8% manganese, and the contents of sulfur and phosphorus are less than 0.02% respectively, and the balance is iron;

[0007] The nanoparticles are composed of one or two of aluminum oxide, titanium dioxide, Y2O3, ZrO2, MgO, TiN, BN, MnS·Al2O3, MnS·TiO2, and TiN·MgO·Al2O3; the particle size of the nanoparticles is in the range of 50 to 300 nm;

[0008] The low alloy steel is Q235, 30 steel or 20Mn2 steel.

[0009] The method for preparing the crusher roller comprises the following steps:

[0010] The first step is to select solid welding wire and use submerged arc welding technology to build up a cladding metal with a single-side thickness of 11 to 13 mm on the surface of the roller;

[0011] The operating parameters of the submerged arc welding are as follows: the working voltage is 29-31V, the current is 450-480A, and the welding speed is 4-6m / min; before surfacing, the roller is preheated to 200-300°C and kept warm for 60-120 minutes;

[0012] The composition of the solid welding wire is 2.0-2.5% nanoparticles, 0.36-0.55% carbon, 4.5-13.5% chromium, 0.2-1.2% silicon, 0-1.2% molybdenum, 0-1.2% vanadium, 0.3-0.8% manganese, less than 0.02% sulfur and phosphorus respectively, and the balance is iron;

[0013] The second step is to anneal the surfacing roller at 250-400°C for 90-150 minutes;

[0014] The third step is to turn the roller surface by 2 to 3 mm to keep the roller surface flat and retain a 9 to 10 mm working layer;

[0015] The fourth step is to heat the mixture to 450-550° C. for 60-120 minutes to obtain a crusher roller.

[0016] The repair method of the pressure roller is as follows: when the working layer is worn by 5 to 6 mm, the pair of rollers is disassembled, the surface of the rollers is turned flat with a lathe, and the first to fourth steps are repeated.

[0017] In the first step, the submerged arc welding in the cladding of the working layer uses TLF601 sintered flux sold on the market.

[0018] The above-mentioned roller body for a crusher, the surfacing process is submerged arc welding commonly used in industry.

[0019] The method for preparing the solid welding wire comprises the following steps:

[0020] The first step is to add the raw materials of the required elements into the smelting furnace according to the raw material ratio of the solid welding wire steel, heat it to 1580-1680℃ at a rate of 8-25℃ / min, keep it warm for 20-30 minutes, perform conventional smelting operations such as deoxidation and slag removal, and then cast it into an ingot;

[0021] The composition is 2.0-2.5% nanoparticle content, 0.36-0.55% carbon content, 4.5-13.5% chromium content, 0.2-1.2% silicon content, 0-1.2% molybdenum content, 0-1.2% vanadium content, 0.3-0.8% manganese content, less than 0.02% sulfur and phosphorus content, and the balance is iron;

[0022] In the second step, the ingot is forged into a square billet and then hot rolled into a wire rod with a diameter of 5.5 to 8.0 mm;

[0023] The third step is to pickle or mechanically grind the surface oxide of the obtained wire rod, and then cold-draw it into a solid welding wire with a diameter of 4.0 to 5.0 mm.

[0024] In the above-mentioned method for preparing a crusher roller, the raw materials and equipment used for roller casting and the equipment used for surfacing welding are all easily obtained through commercial purchase or other channels, and the processes used are all well known in the technical field.

[0025] The essential features of the present invention are:

[0026] An efficient and regenerable wear-resistant layer (thickness is about 3-5% of the roller diameter) is welded on the outer wall of the ordinary carbon steel or low alloy steel roller ring, which not only avoids unnecessary waste caused by multiple turning of a single high manganese steel roller body, but also significantly extends the service life of the roller and saves resources.

[0027] The beneficial effects of the present invention are:

[0028] Compared with the existing high manganese steel roller body, the high-strength roller for crusher and the preparation method thereof of the present invention have significant improvements in:

[0029] ① The working layer of the crusher roller of the present invention can be directly hardened after surfacing welding, and there is no need for the high manganese steel roller to harden only when it is working to crush materials. Therefore, there are no problems such as low hardening degree due to insufficient crushing force and grooves or pits caused by softening of the roller surface.

[0030] ② The working layer of the crusher roller of the present invention is mainly composed of a martensite + bainite matrix with high hardness and good toughness, and fine carbides and oxide hard points dispersed thereon. It has good toughness while maintaining high hardness and high wear resistance, so it is not easy to crack when crushing ore. The working layer of the high-chromium white cast iron composite roller is mainly composed of brittle carbides with high hardness, and easy cracking is a common problem.

[0031] ③ When a crusher roller of the present invention is surfacing welded, the solid welding wire used is drawn from steel containing nano oxide particles, so the hardness of the surfacing layer is high and evenly distributed (±1-2HRC), so that the wear of the roller surface during operation is relatively uniform, which not only significantly improves the utilization rate of the roller working layer, but also prevents the problem of local grooves in the high manganese steel roller during use (the reason is that the hardness distribution is extremely uneven, the maximum hardness of the unhardened layer is only HRC21, while the hardened layer hardness is HRC57.5), which requires disassembly for "turning and peeling", greatly reducing the labor intensity of operators and improving production efficiency.

[0032] ④ When the surfacing working layer of the crusher roller of the present invention is worn to a limit size, it can be disassembled and a new working layer can be re-surfaced on the original roller body, thereby saving about 30-50% of the manufacturing cost of the roller. Description of the drawings:

[0033] Figure 1 The oxide particles in the solid welding wire obtained in Example 1 and the energy spectrum analysis results, wherein: Figure 1 (a) shows the oxide particles distributed on the steel matrix (indicated by arrows). Figure 1 (b) for Figure 1 (a) Energy spectrum analysis results of oxide particles at the position indicated by the arrow;

[0034] Figure 2 The microstructure obtained in Example 2 is the result of surfacing with a solid welding wire to which nano-Al2O3 and TiO2 are added. Specific implementation method:

[0035] Embodiment 1:

[0036] The materials are prepared according to the ratio of 2.2% alumina and titanium dioxide (wherein the mass ratio of alumina and titanium dioxide is 1:1, and the particle size is 50-200 nm) (the percentage is the mass percentage of the steel used for welding wire; the material ratio described later is the same), 0.5% carbon content, 13.0% chromium content, 0.2% silicon content, 0.3% manganese content, 0.01% sulfur and phosphorus content respectively, and the balance is iron. The raw materials of the required elements are added to the smelting furnace (the addition amount of the self-made oxide-containing intermediate alloy accounts for 20% of the total mass of the steel, and the rest are 20 steel, ferrochrome, ferrosilicon and ferromanganese available on the market), the temperature is raised to 1680°C at a speed of 25°C / min, kept warm for 20 minutes, deoxidized and deslagging are carried out, and then cast into an ingot with a diameter of 300 mm. The ingot is forged into a square billet with a width of 65 mm, and then rolled into a wire rod with a diameter of 6.5 mm. The oxide on the surface of the wire rod is removed by pickling, and then it is cold drawn to a solid welding wire with a diameter of 4.0 mm.

[0037] The roller body is cast using Q235 steel, and the outer diameter of the roller body is turned to a size of φ750mmX500mm. The roller body is preheated at 250℃ and kept at temperature for 120 minutes. The solid core welding wire ( Figure 1It is confirmed that the Al2O3 and TiO2 oxides added by the present invention (indicated by the arrows) are indeed present in the prepared welding wire. They are all uniform spherical particles, not only with high roundness, but also with small particle size and narrow distribution range (diameter is about 120-150nm, so it can significantly increase the heterogeneous nucleation core during the phase change of the material, thereby refining its structure and improving its surfacing and mechanical properties.), using TLF601 as flux, using submerged arc welding process, at 29V voltage and 450A current, a working layer with a single-side thickness of 13mm is surfacing on the outer circle of the roller body, and the welding speed is 6m / min. The hardness of the surfacing layer tested is HRC53±0.5. The roller after surfacing is stress-relieved annealed at 250℃ for 150 minutes, and turned 3mm to obtain a smooth and flat roller surface. The hardness test result of the surfacing layer after heat treatment at 450℃X90 minutes is HRC53.5±1.0. After the rollers are cooled to room temperature, they can be assembled on the crusher. Sintered magnesia (where the content of periclase (MgO) is ≥95%, and the content of impurities such as CaO and SiO2 is ≤5%) was crushed in a company in Yingkou City, Liaoning Province. The results show that the service life of the roller working layer with a wear of 5mm (210 days) is three times the total life of the existing high manganese steel rollers (the first service life after installation is one month, and the service life after two disassembly and maintenance is 20 days each, a total of 70 days).

[0038] Embodiment 2:

[0039] The ingredients are prepared according to the ratio of 2.0% alumina (particle size: 100-300nm), 0.36% carbon, 4.6% chromium, 1.2% silicon, 1.2% molybdenum, 0.8% vanadium, 0.8% manganese, 0.01% sulfur, 0.015% phosphorus, and the balance is iron. The raw materials of the required elements are added to the smelting furnace (the addition amount of the self-made oxide-containing intermediate alloy accounts for 20% of the total mass of the steel, and the rest are 30 steel, ferrochrome, ferrosilicon, ferromolybdenum, ferrovanadium and ferromanganese available on the market), and the temperature is raised to 1650℃ at a speed of 8℃ / min, kept warm for 30 minutes, deoxidized and deslaged, and then cast into an ingot with a diameter of 400mm. The ingot is forged into a square billet with a width of 80mm, and then hot rolled into a wire rod with a diameter of 8.0mm. The oxide on the surface of the wire rod is knocked off with a sand belt, and then cold drawn to a solid welding wire with a diameter of 5.0mm.

[0040] The roller body was cast using 30 steel, and the outer diameter of the roller body was turned to a size of φ610mm×400mm. The roller body was preheated at 220℃ and kept at temperature for 90 minutes. The solid welding wire was used, TLF601 was used as flux, and a single-side thickness of 12mm was welded on the outer diameter of the roller body at a voltage of 30V and a current of 480A. The welding speed was 5m / min. The hardness of the welded layer tested was HRC53.5±1.0. Figure 2It is the result of corrosion of the microstructure of the surfacing layer, in which the black needle-like structure is lower bainite with good toughness. The roller after surfacing was stress-relieved and annealed at 300℃ for 120 minutes, and turned 2mm to obtain a smooth and flat roller surface. After heat treatment at 520℃X90 minutes, the hardness of the surfacing layer is HRC56.5±0.5. After the roller cools to room temperature, it can be assembled on the crusher. HBG80 bauxite homogenous material (Al2O3=80.5%, SiO2=13.4%, TiO2=3.45%, Fe2O3=1.45%, CaO and MgO content are 0.6% respectively) was crushed in an enterprise in Xinmi City, Henan Province. The results show that the service life (65 days) of the roller working layer with a wear of 6mm is 2.5 times longer than the one-time life (30 days) of the existing high manganese steel roller body.

[0041] Embodiment 3:

[0042] The ingredients are prepared according to the proportion of 2.1% titanium dioxide (particle size: 80-250nm), 0.55% carbon, 13.5% chromium, 0.5% silicon, 0.6% manganese, 0.008% sulfur, 0.012% phosphorus, and the balance is iron. The raw materials of the required elements are added to the smelting furnace (the amount of self-made oxide-containing intermediate alloy accounts for 20% of the total mass of the steel, and the rest are 20MnSi steel, ferrochrome, ferrosilicon and ferromanganese available on the market), and the temperature is raised to 1580℃ at a rate of 20℃ / min, kept warm for 25 minutes, deoxidized and deslaged, and then cast into an ingot with a diameter of 300mm. The ingot is forged into a square billet with a width of 65mm, and then rolled into a wire rod with a diameter of 5.5mm. The surface oxide of the wire rod is pickled and removed, and then cold drawn to a solid core welding wire with a diameter of 4.0mm.

[0043] The roller body is cast using 20Mn2 steel, and the outer circle of the roller body is turned to a size of φ400mmX250mm. The roller body is preheated at 200℃, kept at temperature for 60 minutes, and the solid welding wire is used with TLF601 as flux. At a voltage of 31V and a current of 460A, a single-side thickness of 11mm working layer is welded on the outer circle of the roller body, and the welding speed is 5m / min. The hardness of the tested welded layer is HRC53.5±1.2. The roller after welded is stress relieved annealed at 400℃ for 90 minutes, and 2mm is turned to obtain a smooth and flat roller surface. After heat treatment at 480℃X60 minutes, the hardness test result of the welded layer is HRC54±1.5. After it cools to room temperature, it can be assembled on the crusher. The electrofused stabilized zirconia balls (ZrO2 content 99.5%, the rest are SiO2, TiO2 and Fe2O3 impurities) were crushed in a company in Xinmi City, Henan Province. The results show that the service life of the roller working layer with a wear of 6mm (40 days) is twice as long as the service life of the existing chromium-molybdenum-manganese alloy steel roller body (20 days). The rollers are disassembled and turned about 2mm to keep the roller surface smooth and flat. The above-mentioned surfacing process is used again to surfacing a working layer with a thickness of 12mm on the outer wall of the roller body. Subsequently, the same heat treatment and machining are used, and the rollers are assembled on the crusher again. The results show that the service life of the roller working layer with a wear of 5mm (40 days) is the same as the first surfacing.

[0044] Embodiment 4:

[0045] According to the ratio of 2.5% alumina and titanium dioxide (wherein the mass ratio of alumina and titanium dioxide is 1:1, particle size: 50-200nm, carbon content is 0.4%, chromium content is 5.2%, silicon content is 0.8%, molybdenum content is 0.9%, vanadium content is 1.2%, manganese content is 0.5%, sulfur content is 0.015%, phosphorus content is 0.012%, and the balance is iron, the raw materials of the required elements (self-made oxide-containing master alloy) are added to the smelting furnace. The amount of steel input accounts for 20% of the total mass of steel, and the rest are 20 steel, ferrochrome, ferrosilicon, ferromolybdenum, vanadium nitrogen alloy and ferromanganese available on the market. The temperature is raised to 1620℃ at a rate of 15℃ / min, kept warm for 30 minutes, deoxidized and deslagging, and then cast into an ingot with a diameter of 400mm. The ingot is forged into a square billet with a width of 80mm, and then rolled into a wire rod with a diameter of 8.0mm. The oxide on the surface of the wire rod is knocked off with a sand belt, and then cold drawn to a solid core welding wire with a diameter of 5.0mm.

[0046] The roller body is cast with Q235 steel, and the outer circle of the roller body is turned to the size of φ750mmX500mm. The roller body is preheated at 300℃, kept at temperature for 120 minutes, and the solid welding wire is used with TLF601 as flux. At 30V voltage and 460A current, a single-side thickness of 12mm working layer is welded on the outer circle of the roller body, and the welding speed is 4m / min. The hardness of the tested surfacing layer is HRC53±1.5. The roller after surfacing is stress-relieved annealed at 400℃ for 120 minutes, and 2mm is turned to obtain a smooth and flat roller surface. The hardness of the surfacing layer after heat treatment at 550℃X120 minutes is HRC56±1. After it cools to room temperature, it can be assembled on the crusher. In a company in Xinmi City, Henan Province, M70 sintered molybdenum (Al2O3 content 72%, SiO2 content 26%, TiO2 and Fe2O3 impurity content 2%) was crushed. The results show that the service life of the roller working layer with a wear of 6mm (65 days) is 3.6 times longer than the one-time life of the existing high manganese steel roller pair (14 days). The roller pair was disassembled and turned about 3mm to keep the roller surface smooth and flat. The above-mentioned surfacing process was used again to surfacing a working layer with a thickness of 12mm on the outer wall of the roller body. Subsequently, the same heat treatment and machining were used, and the roller pair was assembled on the crusher again. The results showed that the service life of the roller working layer with a wear of 5mm (62 days) was equivalent to the first surfacing.

[0047] Matters not covered by the present invention are known technologies.

Claims

1. A pair of rollers for a crusher, characterized in that: The pressing roller of the pair of rollers comprises a roller body and a working layer attached to the surface of the roller body; the thickness of the working layer is 9 to 10 mm; The roller body is cast from carbon steel or low alloy steel, the working layer contains 2.0-2.5% nanoparticles, 0.36-0.55% carbon, 4.6-13.5% chromium, 0.2-1.2% silicon, 0-1.2% molybdenum, 0-1.2% vanadium, 0.3-0.8% manganese, and less than 0.02% sulfur and phosphorus respectively, with the remainder being iron; The nanoparticles are composed of one or two of alumina, titanium dioxide, Y2O3, ZrO2, MgO, TiN, BN, MnS·Al2O3, MnS·TiO2, and TiN·MgO·Al2O3; the particle size of the nanoparticles ranges from 50 to 300 nm; The method for preparing the pair of rollers for a crusher comprises the following steps: The first step is to select solid welding wire and use submerged arc welding technology to build up a cladding metal with a single-side thickness of 11-13 mm on the surface of the roller. The operating parameters of the submerged arc welding are as follows: the working voltage is 29-31 V, the current is 450-480 A, and the welding speed is 4-6 m / min; before surfacing, the roller is preheated to 200-300°C and kept warm for 60-120 minutes; The composition of the solid welding wire is 2.0-2.5% nanoparticles, 0.36-0.55% carbon, 4.6-13.5% chromium, 0.2-1.2% silicon, 0-1.2% molybdenum, 0-1.2% vanadium, 0.3-0.8% manganese, less than 0.02% sulfur and phosphorus respectively, and the balance is iron; The second step is to anneal the surfacing roller at 250-400°C for 90-150 minutes; The third step is to turn the roller surface by 2-3 mm to keep the roller surface flat and retain a 9-10 mm working layer; The fourth step is to heat the material to 450-550°C for 60-120 minutes to obtain a roller for crushing. When the working layer is worn 5 to 6 mm, remove the roller, use a lathe to turn its surface flat, and repeat the first to fourth steps to achieve repair; The method for preparing the solid welding wire comprises the following steps: The first step is to add the raw materials of the required elements into the smelting furnace according to the raw material ratio of solid welding wire steel, heat it to 1580 ~ 1680 ° C at a rate of 8 ~ 25 ° C / min, keep it warm for 20 ~ 30 minutes, deoxidize and remove slag, and then cast it into an ingot; In the second step, the ingot is forged into a billet and then hot rolled into a wire rod with a diameter of 5.5 to 8.0 mm; In the third step, the surface oxide of the obtained wire rod is pickled or mechanically polished, and then cold drawn into a solid welding wire with a diameter of 4.0 ~ 5.0 mm.

2. The crusher roller according to claim 1, characterized in that: The low alloy steel is Q235, 30 steel or 20Mn2 steel.

Citation Information

Patent Citations

  • Super wear-resisting composite roller body of two-roller crushing mill

    CN106140380A

  • Open arc overlaying wire material with strong abrasive resistance for grinding roller and grinding disk

    CN101658980A

  • Metal ceramic grinding roller, and preparation method thereof

    CN104959194A

  • Submerged arc welding wire for high-strength steel and preparing method of wire

    CN108247234A

  • Submerged-arc welding flux-cored wire, BD2 roller and preparation methods of submerged-arc welding flux-cored wire and BD2 roller

    CN114055011A